Inhibition of return (IOR) meets stimulus-response (S-R) binding: Manually responding to central arrow targets is driven by S-R binding, not IOR. Issue 10 (26th November 2022) - Schöpper, Lars-Michael; Frings, Christian
ABSTRACT: Localizing targets repeating or changing their position typically leads to a benefit for location changes, that is, inhibition of return (IOR). Yet, IOR is mostly absent when sequentially responding to arrows pointing to the left or right. Previous research suggested that responding to central arrow targets resembles a discrimination response. For the latter, action control theories expect the modulation of response repetitions and changes by task-irrelevant feature repetitions and changes (e.g., colour), caused by stimulus-response (S-R) binding – a modulation typically absent in localization performance. In the current study, participants gave left and right responses to peripheral targets repeating or changing their position, and to central arrow targets repeating or changing their pointing direction. Targets could repeat or change their colour. For central targets, responses were heavily modulated by colour repetitions and changes, suggesting S-R binding. No S-R binding, but only IOR was found for peripheral targets. Analysis of reaction time percentiles suggested that this pattern was not caused by fast response execution. These results show that S-R binding approaches allow to explain effects typically discussed in the context of attentional orienting, highlighting the similarities of two research strands working in parallel for years without much of exchange.